2020
DOI: 10.3390/nu12082175
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus thermophilus: To Survive, or Not to Survive the Gastrointestinal Tract, That Is the Question!

Abstract: The probiotic market is increasing world-wide as well as the number of products marketed as probiotics. Among the latter, many products contain Streptococcus thermophilus strains at several dosages. However, the scientific evidence that should support the probiotic status of those S. thermophilus strains is often contradictory. This review analyses the scientific literature aimed to assess the ability of S. thermophilus strains to survive the human gastrointestinal tract by discussing the scientific validity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 62 publications
0
41
0
Order By: Relevance
“…In human gut microbiota, Clostridiales order is composed of a high variety of commensals and opportunistic species while Streptococcus genus contains a probiotic species named S. thermophilus and commensal species such as S. salivarius and S. vestibularis . In particular, this latter genus is involved in urea metabolism and lactic acid production, and its metabolites may favor a pH environment that promotes commensal bacteria survival [ 53 ]. In agreement with our discussion, several authors have suggested that Clostridia and Streptococcus may be potential drivers of population dynamics in the intestine, capable of influencing microorganism interactions and gut homeostasis [ 52 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In human gut microbiota, Clostridiales order is composed of a high variety of commensals and opportunistic species while Streptococcus genus contains a probiotic species named S. thermophilus and commensal species such as S. salivarius and S. vestibularis . In particular, this latter genus is involved in urea metabolism and lactic acid production, and its metabolites may favor a pH environment that promotes commensal bacteria survival [ 53 ]. In agreement with our discussion, several authors have suggested that Clostridia and Streptococcus may be potential drivers of population dynamics in the intestine, capable of influencing microorganism interactions and gut homeostasis [ 52 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was established that hydrogels made of γ-PGA and sugar alcohol improve the survivability of Lactobacillus strains subjected to acidic conditions. In the next step, the protective effects of developed hydrogels were investigated towards another probiotic strain sensitive to gastrointestinal tract conditions-Streptococcus thermophilus [27]. Free cells of Streptococcus thermophilus and cells entrapped into PGA-E, PGA-X and PGA-S hydrogels were subjected to pH 2.0 up to 4 h (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its technological importance, STH has also gained interest in recent years as a probiotic bacterium [ 25 ]. Many commercial probiotic products available on the market all over the world contain STH [ 26 ], although its ability to survive the stomach environment can be questionable for a probiotic [ 25 , 27 ]. The presence of STH in fermented products has been linked to various beneficial effects on human health, including alleviation of lactose intolerance [ 28 ], inhibition of pathogens [ 29 ], prevention of diarrhea [ 30 , 31 ], modulation of inflammation and cytokine production [ 32 36 ], reduction of uremia [ 37 ], decrease of total cholesterol and low-density lipoprotein cholesterol [ 38 , 39 ], prevention of the development of insulin resistance and improvement of glycemic parameters [ 40 , 41 ], reduced risk of developing certain cancers [ 42 44 ], prevention or treatment of inflammatory gut diseases [ 14 , 45 – 47 ] and maintain gut homeostasis [ 48 ].…”
Section: Introductionmentioning
confidence: 99%